PENGARUH PERTUMBUHAN PENJUALAN DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK YANG DIMODERASI KEPEMILIKAN INSTITUSIONAL - Wulan Nur Khasanah; Titiek Puji Astuti; Faiz Rahman Siddiq (JURNAL ILMIAH EDUNOMIKA, 2025)
Purpose: This study aims to determine the effect of leverage and sales growth on tax avoidance with institutional ownership as a moderator in mining companies listed on the Indonesia Stock Exchange in the period 2016-2023. Methods: The data used in this study is to use secondary data, the population in this study is all mining companies published on the Indonesia Stock Exchange whose samples amount to 110 observations. The sample selection method uses purposive sampling method with panel data regression analysis using eviews 10. Findings: The results showed that sales growth has a negative effect on tax avoidance, meaning that the higher the sales growth, the lower the tax avoidance, while leverage has no effect on tax avoidance. However, the results of this study found that institutional ownership was unable to moderate the effect of sales growth and leverage on tax avoidance. Novelty: The novelty in this study is the addition of moderating variables, namely institutional ownership. Keywords: Tax avoidance, leverage, sales growth, and institutional ownership.